Universitetsstyrning mot minskad andel studieavhopp och ökad studentgenomströmning : En fallstudie av Luleå tekniska universitet - Jonsson, Sebastian; Klyuchko, Anastasiya (2016)
Growing number of the ungraduated students has become a problem for Swedish universities, in particular for public universities, such as Luleå University of Technology. Previous studies in other countries acknowledge that the main reasons for dropping out vary, as they are specific for each university and depend on legislation and other government systems in the respective country. To determine the reasons of the student dropout is not the only challenge for the universities. The next step is to achieve the reduction in dropout rate and to manage the establishment from the perspective of its capacity and this study finding. Luleå University of Technology is one of 47 higher educational establishments in Sweden. The university apparently applies balanced management that can be compared to the management with the balanced scorecard. The balanced scorecard has originally been developed for flexible profit organizations. The purpose of the study is to find out the dropout motives, explain their essence, and explore how the university management handles the situation to decrease the dropouts and improve graduation rates. Empirical information that has been collected during the research is compared to previous studies in the field. The conclusions of the study have been made upon the analysis of the information collected. Other reflections, particularly on how to manage the university towards the above-mentioned objectives, are presented at the end of the investigation. This qualitative study has been conducted with 40 former students from Luleå University of Technology, who expressed their dropout reasons. Those reasons are compared with the answers given by the personnel at Luleå University of Technology, who have processed the student retention issues. Later, the employees, who are expected to use balanced management in their everyday job, describe their approach to the matter. Contrary to our expectations, the dropout reasons were ambiguous and interrelated. At the same time, it was a challenge to determine the ...